Investigation of Genotype by Environment Interactions for Seed Zinc and Iron Concentration and Iron Bioavailability in Common Bean - Katuuramu, Dennis N.; Wiesinger, Jason A.; Luyima, Gabriel B.; Nkalubo, Stanley T.; Glahn, Raymond P.; Cichy, Karen A. (Frontiers in Plant Science, 2021)
Iron and zinc malnutrition are global public health concerns afflicting mostly infants, children, and women in low-income and middle-income countries with widespread consumption of plant based diets. Common bean is a widely consumed staple crop around the world and is an excellent source of proteins, fiber, and minerals including iron and zinc. Development of nutrient dense common bean varieties that deliver more bioavailable iron and zinc with a high level of trait stability requires measurement of the contributions from genotype, environment, and genotype by environment interactions. In this research, we investigated the magnitude of genotype by environment interaction for seed zinc and iron concentration and seed iron bioavailability using a set of nine test genotypes and three farmers’ local check varieties. The research germplasm was evaluated for two field seasons across nine on-farm locations in three agro-ecological zones in Uganda. Seed zinc concentration ranged from 18.0 to 42.0 µg g-1 and was largely controlled by genotype, location, and the interaction between location and season (28.0, 26.2, and 14.7% of Phenotypic Variability Explained [PVE] respectively). Within a genotype, zinc concentration ranged on average 12 µg g-1 across environments. Seed iron concentration varied from 40.7 to 96.7 µg g-1 and was largely controlled by genotype, location, and the interaction between genotype, location, and season (25.7, 17.4, and 13.7% of PVE respectively). Within a genotype, iron concentration ranged on average 28 µg g-1 across environments. Seed iron bioavailability ranged from 8 to 116 % of Merlin navy control and was largely controlled by genotype (68.3% of PVE). The red mottled genotypes (Rozi Koko and Chijar) accumulated the most seed zinc and iron concentration while the yellow (Ervilha and Cebo Cela) and white (Blanco Fanesquero) genotypes had the highest seed iron bioavailability and performed better than the three farmers’ local check genotypes (NABE-4, NABE-15, and Masindi yellow). The genotypes with superior and stable trait performance, especially the Manteca seed class which combine high iron and zinc concentration with high iron bioavailability would serve as valuable parental materials for crop improvement breeding programs aimed at enhancing the nutritional value of the common bean.